2004
DOI: 10.1021/jp049084e
|View full text |Cite
|
Sign up to set email alerts
|

Confined Plasmons in Nanofabricated Single Silver Particle Pairs:  Experimental Observations of Strong Interparticle Interactions

Abstract: We report on the optical properties of single isolated silver nanodisks and pairs of disks fabricated by electron beam lithography. By systematically varying the disk size and surface separation and recording elastic scattering spectra in different polarization configurations, we found evidence for extremely strong interparticle interactions. The dipolar surface plasmon resonance for polarization parallel to the dimer axis exhibited a red shift as the interdimer separation was decreased; as expected from previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

65
556
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(631 citation statements)
references
References 49 publications
65
556
0
1
Order By: Relevance
“…By doing so, we are able to relate the results of the optical response from different approximations and predict the influence of nonlocality in the limit of subnanometric distances where nonlocal effects are pronounced. In elucidating the major physics behind the nonlocal response in plasmonic nanoparticle dimer, we find a robust plasmon ruler [18][19][20][21][22] that unambiguously determines the spectral position of surface plasmon resonances in strongly coupled systems forming subnanometric plasmonic cavities.To implement the TDDFT calculations, a cylindrical jellium model is adopted to describe the electronic structure of the infinite metallic nanowire. This model captures the collective plasmonic modes of conduction electrons and is perfectly suited to address nonlocal effects derived from the interactions between these electrons, such as the dynamical screening of the external field [1,4,5] and tunneling [23][24][25][26][27] as discussed below.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…By doing so, we are able to relate the results of the optical response from different approximations and predict the influence of nonlocality in the limit of subnanometric distances where nonlocal effects are pronounced. In elucidating the major physics behind the nonlocal response in plasmonic nanoparticle dimer, we find a robust plasmon ruler [18][19][20][21][22] that unambiguously determines the spectral position of surface plasmon resonances in strongly coupled systems forming subnanometric plasmonic cavities.To implement the TDDFT calculations, a cylindrical jellium model is adopted to describe the electronic structure of the infinite metallic nanowire. This model captures the collective plasmonic modes of conduction electrons and is perfectly suited to address nonlocal effects derived from the interactions between these electrons, such as the dynamical screening of the external field [1,4,5] and tunneling [23][24][25][26][27] as discussed below.…”
mentioning
confidence: 95%
“…By doing so, we are able to relate the results of the optical response from different approximations and predict the influence of nonlocality in the limit of subnanometric distances where nonlocal effects are pronounced. In elucidating the major physics behind the nonlocal response in plasmonic nanoparticle dimer, we find a robust plasmon ruler [18][19][20][21][22] that unambiguously determines the spectral position of surface plasmon resonances in strongly coupled systems forming subnanometric plasmonic cavities.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…HGN aggregates are also known to exhibit both hybridized plasmon modes, which are the result of surface plasmon interactions with cavity plasmon modes, and collective charge transfer resonances [296][297][298]. However, even when not in direct contact with one another there is an intensification of the dipole charge at the interparticle gap of nanoparticle aggregates in near field proximity [8,[299][300][301]. For example, Xu et al observed that the junction between two nanoparticles 1 nm apart exhibited an EM field enhancement of 10 10 compared to an individual particle [302].…”
Section: Plasmon Coupling In Aggregates For Sersmentioning
confidence: 99%
“…Mais recentemente eles obtiveram experimentalmente o espectro do plasmon de superfícies de pares isolados de nanodiscos de Ag, utilizando um microscópio óptico no modo "dark field", e mostraram que, quando a polarização da radiação incidente é paralela ao eixo interpartículas, é possível observarem-se efeitos de confinamento de plasmon e desvio da banda para o vermelho 48 . Este efeito, que corresponde ao surgimento de um campo elétrico muito intenso no espaço entre as duas partículas metálicas, tornase maior quanto menor for a distância entre elas, indicando um maior acoplamento entre seus plasmons.…”
Section: Plasmon De Superfície E Espectros De Extinçãounclassified